Economic gains using organic P source and inoculation with P-solubilizing bacteria in sugarcane - Antonio M. M. Silva; Lucas S. Pimenta; Xue Qi; Elke J. B. N. Cardoso (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Biological agribusiness has grown substantially worldwide and requires efficient strategies to maintain or increase crop production. However, little is known about the real economic gains associated with belowground mechanisms in agriculture, including those of traditional crops such as sugarcane. This study aimed to identify potential microbiological indicators related to yield increase and value the soil microbiological services through the development of a structural equation model (SEM). The SEM was constructed based on a dataset from a previous sugarcane field experiment in which the effects of inoculation with phosphate-solubilizing bacteria (PSB) and the input of organomineral fertilizer were evaluated. The SEM indicated that the β-glucosidase and alkaline phosphatase activities were potential indicators of yield increases in four scenarios (current, plausible, optimistic, and futuristic). Increases of 158 and 195 t ha-1 were projected based on the β-glucosidase activity for the current and plausible scenarios, respectively. These increases resulted in economic gains of R$ 453.02 ha-1 (US$ 86.07 ha-1) for the current scenario, and R$ 1,571.53 ha-1 (US$ 298.59 ha-1) for the plausible scenario, considering the exchange rate from February 2022 (R$ 0.19 US$-1). Regardless of the scenario, bacterial inoculation was associated with increased β-glucosidase or alkaline phosphatase activity and higher yields, which translates into economic gains for sugarcane farmers.